Produção de herbicida por fermentação submersa apartir do fungo Phoma sp. em biorreator - Brun, Thiarles (2016)
There are several factors that affect the productive potential of crops, among them the incidence of weeds. Chemical control is the predominant method used for weed control because it is more efficient, but when used incorrectly, leaves serious consequences to living and the environment. The use of metabolites produced by fungi with potential herbicide is presented as a good alternative to reduce impacts of synthetic herbicides to the environment. For this, the optimization of production is needed to ensure the viability of the process. The objective of this work was to produce a herbicide by submerged fermentation with effect on the species of Cucumis sativus var. visconsin (cucumber) and Sorghum bicolor (sorghum) and to carry out the chemical characterization of the compounds present in the fermentation broth by gas chromatography. This study was conducted in bioprocess laboratory and in a greenhouse at the Federal University of Santa Maria. The preparation of the pre-inoculum with Phoma sp. was performed by cultivation on shaker under orbital agitation of 120 rpm and 28°C for 5 days. The variables studied in the submerged stirred thank bioreactor were stirring rate (40, 50, and 60 rpm) and aeration (1, 2 and 3 L.min-1 ) for 7 days, when biomass was separated and . After every seven days, was performed to separate the biomass and the fermentation broth containing the phytotoxin. To assess the potential herbicidal some the bioassays used to determine the effectiveness of bioherbicide were tests in pre-emergence, post-emergence and in a detached leaves of Cucumis sativus var species. wisconsin (cucumber) and Sorghum bicolor (sorghum). The results of the bioassays indicate that metabolites produced by Phoma sp. have herbicidal effect on the studied species. The greatest potential herbicide found in both trials was in T3 for the species Cucumis sativus and T4 for Sorghum bicolor. The bioherbicide showed showed 100% inhibition of germination of both species in the pre-emergence tests. From detached leaves tests was verified yellowish lesions in Cucumis sativus and necrotic lesions on leaves of Sorghum bicolor. For the post-emergence test, it was observed a variation of the phytotoxicity from 25 to 66% for the species Cucumis sativus and from 32 to 58% by Sorghum bicolor. The evaluation of plant height, green dry and matter mass there was little difference among the treatments, but it was essential for selecting the best treatment. The application of secondary metabolites produced by submerged fermentation of Phoma sp. present action herbicide pre-emergence, post-emergence and detached leaves of Cucumis sativus and Sorghum bicolor and can become alternative in the future for weed control.